First aid for head trauma at the accident site: Round Table Treatments for brain injuries in the interior of the country; coordinator and introduction Román Arana Iñiguez - Benedek, Pedro (Cirugía del Uruguay, 1973)
In 70% of traffic accidents, head trauma occurs (11) and one in three victims is a multiple trauma patient (12).